States Raise Proficiency Standards in Math and Reading - Peterson, Paul E; Ackerman, Matthew (Education next, 2015)
Since No Child Left Behind (NCLB) was enacted into federal law in 2002, states have been required to test students in grades 3 through 8 and again in high school to assess math and reading achievement. The federal law also asks states to establish the performance level students must reach on the exams in order to be identified as "proficient." NCLB also requires the periodic administration of tests in selected subjects to a representative sample of students in 4th and 8th grade as part of the National Assessment of Educational Progress (NAEP), also known as the nation's report card, which is administered under the auspices of the U.S. Department of Education. The availability of data from both NAEP and from tests administered by each state allows for periodic estimates of the rigor of each state's proficiency standards. Since NCLB was enacted into law, "Education Next" has used this information to identify the rigor of state proficiency standards each time the results from state and NAEP tests have become available. This is the sixth in a series of reports that grade state proficiency standards on the traditional A-to-F scale used to evaluate students. Each state is graded according to the size of the differential between the percentages of students identified as proficient by the state and the percentages identified by NAEP on the 4th- and 8th-grade math and reading exams. In this article, the authors extend the five prior analyses by identifying the changes in state proficiency standards between 2011 and 2013, the last year for which the relevant information is available. They show that many states have raised their proficiency bars since 2011. Indeed, the 2013 data reveal that for the first time, substantially more states have raised their proficiency standards than have let those standards slip to lower levels. Overall, 20 states strengthened their standards, while just 8 loosened them.